Amphiphilic engineering of reduced graphene oxides using a carbon nitride coating for superior removal of organic pollutants from wastewater. (30th October 2021) - Li, Meng; Li, Qiuhan; Xu, Mengwen; Liu, Bowen; Calatayud, David G.; Wang, Lidong; Hu, Zhigang; James, Tony D.; Mao, Boyang
Abstract: Amphiphilic carbon nitride (g-C3 N4 ) was decorated onto reduced graphene oxide (rGO) to obtain rGO-g-C3 N4 composites as excellent adsorbents for the removal of aromatic organic compounds from industrial wastewater. The as obtained rGO-g-C3 N4 composites are effective adsorbents for organic compounds due to the amphiphilic g-C3 N4 . We propose a new adsorption model using an amphiphilic additive which can enhance the water accessibility and hydrophobic interactions between rGO with organic compounds in aqueous media. Where, even water-soluble organic molecules like rhodamine B (RhB) have a high adsorption capability for the rGO-g-C3 N4 (520 mg g −1 ). Molecular dynamics simulations were used to investigate the interactions between RhB and rGO-g-C3 N4 and indicated that amphiphilic g-C3 N4 accelerates the adsorption process. In addition, the amphipathic adsorption approach is enhanced as the salinity of water increases, which can offer great operational flexibility and versatility. This research demonstrates that the highly efficient interactions between aromatic organic molecules and amphiphilic carbon-based nanomaterials can be used for practical applications. Graphical abstract: Image 1 Highlights: An amphipathic strategy was developed for organic pollutants removal. rGO-g-C3 N4 exhibited excellent adsorption performance for aromatic organic pollutants. Molecular dynamics simulation verified amphipathicity enhanced adsorption mechanism. Investigation of the rGO-g-C3 N4 absorption behavior of GO-g-C3 N4 under complex conditions. A rGO-g-C3 N4 membrane was fabricated and tested using lab-scale cross flow experiments.